A economia criativa e os pontos de cultura : uma agenda de cooperação para o desenvolvimento local - Pacheco, Adriano Pereira de Castro (2016)
This study, prepared under the Administration Master's Program, presents the Creative Economy (CE) - concept adjusted to the delicate balance between economic imperatives and the heritage of a nation - in a strategic perspective to local development. Despite the transdisciplinary nature of the CE, this study intends to integrate the theoretical and institutional space that still is under discussion, which moves between the proper formulation and implementation of tools that can stimulate it as public policies and the recognition of tendencies and characteristics that shape the Brazilian CE, from community-based experiences. The fact is that with the possibilities presented by the new economy, the Creative one, it is essential to the understanding of the transition process experienced by the world economy, from the observation of the theoretical foundations and global motivators that compose its structure, having as example the Creative industry and its trajectory. In an attempt to identify to what extent the CE can contribute to inclusive and equitable local development in the social, cultural and economic dimensions, this study made use of discourse and content analysis methods, having as the main object of analysis the Culture points, specifically the Sapicuá Pantaneiro and Moinho Cultural Sul - Americano, present in Mato Grosso do Sul‘s Pantanal mesoregion. The results show that the Culture Points may include potential production centers of the CE and subjected to some interaction variables with the traditional production system can integrate new economic circuits based on products and services that have the symbolic dimension as its value determinant.